Structural peculiarities of shoots of switch grass (Panicum virgatum L in the context of introduction in the Right-Bank Forest-Steppe and Polissia zones of Ukraine - Т. О. Щербакова; Д. Б. Рахметов (Plant Varieties Studying and Protection)
Purpose. To define morphological peculiarities of the different types of shoots of switch grass (Panicum virgatum L.) in the context of introduction in the Right-Bank Forest-Steppe and Polissia zones of Ukraine.